Neonatal piglets mesocolon edema and colitis due to Clostridium difficile infection: prevalence, clinical disease and pathological studies - Cappuccio , Javier A.; Quiroga , Maria A; Moredo , Fabiana A.; Canigia, Liliana F.; Machuca , Mariana; Capponi , Osvaldo; Bianchini , Ariel; Zielinski , Gustavo; Sarradell , Javier; Ibar , Mariela; Vigo , Germán B.; Giacoboni , Gabriela; et al. (Brazilian Journal of Veterinary Pathology, 2009)
Clostridium difficile is a Gram-positive opportunistic anaerobic bacterium found in the soil, water as well as the digestive tract of several species of mammals. Currently in high-health herds and not related with antibiotic treatment, C. difficile has been emerged in association with neonatal catarrhal, fibrinous or purulent colitis in 2 to 7 day-old piglets. Mesocolon edema and colitis with a “volcano" lesion are pathological key marks of C. difficile infection. In farm 1, the prevalence of neonatal piglet mesocolon edema and colitis was evaluated in an extensive study of postmortem preweaning mortality. Lectinhistochemistry pattern of normal colon and colon with edema and colitis were analyzed in order to provide more accurate information related with pathogenesis of C.difficile infection. In farm 2, a clinical description of an outbreak of neonatal colitis in piglets due to C. difficile infection was reported. A total 820 piglets were post-mortem examined, from them, 8 cases were classified as suspected of C. difficile infection (0.1%). Age of affected piglets varied between 3 to 14 days. In all of them, the key mark was the severe mesocolon edema and 2 cases were characterized by focal necrosis and loss of epithelial cells associated with a focal infiltration of neutrophils and macrophages in the lamina propria and lumen like erupted volcano. Lectins SBA and DBA that has affinity to α Gal epitope were negative in normal samples but reacted strongly positive at the glycocalix of the villi enterocytes of the affected samples indicating a change in the carbohydrates pattern of the cells surfaces that might favor the binding of C. difficile toxin A (TcdA). In farm 2, from 11 examined piglets, 6 of them (54%) showed different degree of mesocolon edema and in only 2 of them; volcano lesions were the main histopathological findings. Rectal swab from 8 diarrheic and 5 postmortem examined piglets were surveyed for eltA estI estII and stx2e virulence gens of E. coli and all samples were negative. Clostridium difficile toxins A and B were identified only in the sample with severe gross and microscopic changes. Isolation of C. difficile was unsuccessfully. Infection of C. difficile is present in Argentinean pig farms. Diagnosis of subclinical infection might be negligent if post-mortem studies of preweaning mortality at weekly intervals are not performed. However, when clinical disease appeared, mortality might be high as it was reported in the farm 2. Comparative lectinhistochemistry studies from field cases added further information of the carbohydrates present on glycocalix of villi enterocytes related with toxin receptors.